Learning about Social Entrepreneurship and Management in Times of Social Transformation - Langergaard, Luise Li.; Dupret, Katia; Eschweiler, Jennifer (Cham : Springer International Publishing : Imprint: Springer, 2023)
The book brings together perspectives on entrepreneurship research, education and practice to understand social entrepreneurship in its wider societal, political and economic context. Its unique contribution comes from its interdisciplinary approach that spans from the societal to the organizational level, with specific focus social innovation and management. It views management of social entrepreneurship and social enterprise in light of its societal context and employs social innovation to critically assess social entrepreneurship as driver of change. The emergence of social entrepreneurship as an academic field is linked to several societal trends such as public austerity, financial crises, new social challenges and a growing counter-movement to globalised capitalism. Generally seen as organisations serving both social and economic objectives, social enterprises, social innovation and social entrepreneurship have their roots in civil society, civic activism or the solidarityeconomy, but also manifest themselves as for-profit companies, with new organisational forms emerging and old ones changing. The contributions in this book elucidate these developments and the role of social entrepreneurs and social enterprises. Furthermore, the book offers great insight into the specific ways of managing, leading and creating innovation in social enterprises as well as perspectives on how to understand their social impact or value creation. .
Chapter 1. Introduction. Learning about Social Entrepreneurship and Management in Times of Social Transformation -- Chapter 2. The Solutions to the Future are Problem-Oriented: The intersection between social entrepreneurship, sustainable skills, and problem-oriented project learning -- Chapter 3. The role of the social entrepreneur when designing for social sustainability -- Chapter 4. Participation in social innovation processes: a case study of Roskilde University Impact Hub -- Chapter 5. Social Entrepreneurship and the governance context of Areas of Limited Statehood -- Chapter 6. Socially responsible innovation between corporate social responsibility and social entrepreneurship. Towards holistic integration of stakeholder management, ethics, and sustainable development goals -- Chapter 7. Leadership of social entrepreneurship in a multi-stakeholder context: A specific domain or specific contextualities of leadership theories? -- Chapter 8. How is social innovation emerging in the Danish humanitarian sector? -- Chapter 9. Evaluating Social Impact -- Chapter 10. Arts-based creativity and culture in social entrepreneurship -- Chapter 11. Do we need utopia for a theory of social innovation as social change?
Keywords: Nonprofit organizations; Business ethics; Economic sociology; Education -- Philosophy; Non-Profit Organizations and Public Enterprises; Business Ethics; Economic Sociology; Educational Philosophy